The Knowledge Economy: How Intellectual Capital Drives Financial Performance of Non-financial Service Firms in Nigeria - Umar, Adamu; Dandago, Kabiru Isa (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
The study investigates the relationship between intellectual capital and financial performance of 58 listed non-financial service firms in Nigeria for a period of eleven years from 2012 to 2022.The study extracts data from annual reports and accounts of the listed non-financial service firms in Nigeria. The study aligns with correlational research design and positivism research philosophy. The modified Value-added intellectual coefficient (MVAIC) method is applied to measure the value-based intellectual performance of the sampled firms. Return on equity (ROE) and Tobin’s (TQ) are used to measure the financial performance of the firms. The intellectual capital (human and structural and relational capital) of selected firms has been analyzed and their impact on financial performance has been measured using the multiple regression technique. The findings of the analysis reveal that the relationships between intellectual capital and financial performance indicators, namely ROE and TQ, are varied. The study results suggest that intellectual capital influences the financial performance of Nigeria’s listed non-financial service firms. The study recommends that the board of directors of non-financial service firms in Nigeria should identify, protect and ensure effective utilization of intellectual capital in their companies in order to achieve long-term success and competitiveness. The study provides policy implications as the MVAIC method can be used as an important tool by decision-makers in the knowledge economy to integrate intellectual capital in the decision-making process.